Tomato leaf disease detection using Resnet-50 and MobileNet Architecture - Tahamid, Abu (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2020.